Angular Rate Sensor Joint Kinematics Applications - Gregory W. Hall; Jeff R. Crandall; Gregory S. Klopp; Walter D. Pilkey (Shock and Vibration)
High speed rotary motion of complex joints were quantified with triaxial angular rate sensors. Angular rate sensors were mounted to rigid links on either side of a joint to measure angular velocities about three orthogonal sensor axes. After collecting the data, the angular velocity vector of each sensor was transformed to local link axes and integrated to obtain the incremental change in angular position for each time step. Using the angular position time histories, a transformation matrix between the reference frame of each link was calculated. Incremental Eulerian rotations from the transformation matrix were calculated using an axis system defined for the joint. Summation of the incremental Eulerian rotations produced the angular position of the joint in terms of the standard axes. This procedure is illustrated by applying it to joint motion of the ankle, the spine, and the neck of crash dummies during impact tests. The methodology exhibited an accuracy of less than 5% error, improved flexibility over photographic techniques, and the ability to examine 3-dimensional motion.